A review on Borreria verticillata: A potential bionematicide, channeling its significant antimicrobial activity against root-knot nematodes - Nkechi B. Izuogu; Oluwatoyin E. Bello; Oluwasesan M. Bello (Heliyon, 2020)
Phytopesticides are human-friendly beside been easily accessible and bio-degradable, are therefore environmentally friendly compared to the synthetic pesticides which huge adverse effects on human, animals and the ecosystem. Plants are large reservoir of secondary metabolites largely untapped or under-tapped for use as pesticides. One problem associated with this is to identify plants which can be assessed and further exploited for this use. Borreria verticillata belongs to Rubiaceae, it is native to South Americas but gained popularity globally. It is known as a weed, showing resistance to many synthetic pesticides and can be grown on a wide range of soil types. B. verticillata is used traditionally against skin diseases such as eczema, infectious dermatitis and scabies. Its antimicrobial application is large and efficient as revealed by most authors. This article inclines to propose and offer current studies with information on the various application of this plant species against various microorganisms, thereby extending its use against plant parasitic nematodes which cause severe yield losses to numerous agricultural crops. Most search engines, journals and dissertation search engines i.e. Google scholar, pubmed, sciencedirect, scopus, web of science, springer, elsevier, like Open-thesis, OATD, ProQuest and EthOs were queried by employing titles such as B. verticillata, Borreria verticillata and biological activity of B. verticillata. The most synonymous name was queried too i.e. Spermacoce verticillata. This review suggests a main point about this resistant weed i.e. its significant antimicrobial activity. It further emphases the need exploits this useful effect against nematodes since they are microorganisms. Phytochemistry of the B. verticillata was gathered in this study and the compounds isolated from the plant i.e. terpenes, iridoids, flavonoids and alkaloids (29 compounds) further provide a basis for a significant antihelmintic effect. The review concludes on the need to extends its antimicrobial activity to sustainable agriculture. Since it is a very common plant in Nigeria, it is easily accessible to farmer protect their cultivations from plant-parasitic nematode attacks.